PEPTIDYL ALDEHYDE DERIVATIVE AND ITS USE - INOUE ATSUSHI; NAKAMURA MASAYUKI; AZUMA MITSUYOSHI; YOSHIDA HIROYOSHI (1998)
PROBLEM TO BE SOLVED: To obtain the subject new compound having a strong cysteine protease activity and especially useful for preventing and treating cataract. SOLUTION: A compound of formula I [R is a 1-4C alkyl, a (substituted) 6-10C aryl; R , R are each H, a 1-4C alkyl, etc.; R is a (substituted) lower alkyl]. For example, N-(2-naphthalenesulfonyl)-L-valyl-L-leucinal. The compound of formula I is obtained by subjecting a sulfonyl chloride and a compound of formula II (e.g. glycine) to Schotten-Baumann reaction, condensing the obtained compound of formula III with N-hydroxysuccinic acid imide in the presence of a condensing agent (e.g. N,N-dicyclohexylcarbodiimide), reacting the obtained compound of formula IV with an aminoalcohol in the presence of a base in a solvent such as tetrahydrofuran, and subsequently oxidizing the obtained compound of formula V. The compound is orally administered at a does of 1-50mg, when used for cataract.